Defining the Church of England in Italy in the Early Modern Times: British Reconciliations in the Documentation of the Inquisition of Pisa - Stefano Villani (Etudes Epistémè)
The documents of the Roman Inquisition evidence the semantic embarrassment of the Inquisitors to define the members of the Church of England. The expression “of the Anglican sect of Protestants” is very rarely used for them. More often the British are defined as Calvinists or as Lutherans, more rarely as “Protestant heretics of England”, or as of the “mixed religion, part of Luther and part of Calvin.” The schemes crystallized in the Inquisitorial manuals present a conceptual framework that obviously did not work well for Protestants who were neither Lutherans nor Calvinists. The mechanical application of these uncertain definitions demonstrates not only the lack of a more sophisticated interpretative paradigm but also the bureaucratic nature of many of the inquisitorial proceedings.